2010
DOI: 10.1371/journal.pone.0010572
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of a Q-ter® Based Nutritional Mixture on Functional Performance, Mitochondrial Function, and Oxidative Stress in Rats

Abstract: BackgroundMitochondrial dysfunction and oxidative stress are central mechanisms underlying the aging process and the pathogenesis of many age-related diseases. Selected antioxidants and specific combinations of nutritional compounds could target many biochemical pathways that affect both oxidative stress and mitochondrial function and, thereby, preserve or enhance physical performance.Methodology/Principal FindingsIn this study, we evaluated the potential anti-aging benefits of a Q-ter® based nutritional mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…Indeed, decreased CoQ content can lead to the inactivation of respiratory chain enzymes (Matthews et al, 1998), inducing a vicious cycle in which the impaired enzymes enhance ROS production (ForsmarkAndrée et al, 1997). Our AC morphological alterations as well could be consistent with data reporting spine loss either after the induction of oxidative stress (Avila-Costa et al, 2001;Zaja-Milatovic et al, 2008) or with oxidative damage after noise exposure (Cheng et al, 2011) or visual sensory deprivation (Hernandes et al, 2010). However, the decreased cortical CoQ 9 and CoQ 10 levels at days 1 and 11 in the Noise group are, more likely, a consequence of changes in metabolic activity attributable to afferent inactivity and upward spread of cochlear damage (Gröschel et al, 2010).…”
Section: Cochlear Redox Statussupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, decreased CoQ content can lead to the inactivation of respiratory chain enzymes (Matthews et al, 1998), inducing a vicious cycle in which the impaired enzymes enhance ROS production (ForsmarkAndrée et al, 1997). Our AC morphological alterations as well could be consistent with data reporting spine loss either after the induction of oxidative stress (Avila-Costa et al, 2001;Zaja-Milatovic et al, 2008) or with oxidative damage after noise exposure (Cheng et al, 2011) or visual sensory deprivation (Hernandes et al, 2010). However, the decreased cortical CoQ 9 and CoQ 10 levels at days 1 and 11 in the Noise group are, more likely, a consequence of changes in metabolic activity attributable to afferent inactivity and upward spread of cochlear damage (Gröschel et al, 2010).…”
Section: Cochlear Redox Statussupporting
confidence: 91%
“…We selected the exogenous antioxidant coenzyme Q 10 (CoQ 10 ) analog because, in addition to its role in mitochondrial respiration and electron transport chain, CoQ acts as a potent antioxidant by either directly scavenging free radicals or recycling and regenerating other antioxidants (Bhagavan and Chopra, 2006;Lenaz et al, 2007). Furthermore, CoQ 10 is known for its benefits in pathologies that exhibit impaired mitochondrial bioenergetic function and/or increased oxidative damage (Xu et al, 2010). In particular, we used a CoQ 10 water-soluble formulation (Q ter ) because we demonstrated that it shows enhanced bioavailability with respect to the native form (Bergamini et al, 2012) and promotes outer hair cell (OHC) survival in a guinea pig NIHL model (Fetoni et al, 2009(Fetoni et al, , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To optimize energy production and minimize oxidative damage, mitochondria are engaged in dynamic network exchange through fission and fusion, which identifies damaged mitochondrial and tags them for mitophagy [11], [12]. Impairments of these mechanisms of mitochondrial quality control during aging contribute to the age-related increase in tissue oxidative damage and functional decline [13], [14], [15], [16], [17]. Aerobic exercise is an effective physiological intervention that counteracts aging-related mitochondrial dysfunction through simultaneous improvement of mitochondrial biogenesis and quality control, including up-regulation of mitophagy [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence, mainly indirect, that exogenous orally administered CoQ 10 may be incorporated into mitochondria, at least in conditions of partial CoQ tissue deficiency, where it may enhance electron transfer and ATP synthesis with improvement of the disease both in human and animal studies, e.g. in genetic CoQ 10 deficiency [Rötig et al, 2000;Di Giovanni et al, 2001;Quinzii and Hirano, 2010], cardiac failure [Rosenfeldt et al, 2005;Molyneux et al, 2009], Parkinson's disease [Matthews et al, 1998], Alzheimer's disease [Yang et al, 2010], Friedreich's ataxia [Hart et al, 2005], and aging [Xu et al, 2010]. The major problem of CoQ 10 administration is its low bioavailability due to its extreme hydrophobicity [Beg et al, 2010].…”
Section: What We Expect From Coq Deficiency and Supplementationmentioning
confidence: 99%
“…A water-soluble formulation (Qter) has recently been shown to be easily incorporated into cultured cells and their mitochondria, enhancing respiration and antioxidant properties [Bergamini et al, 2012]. The same formulation was found to improve grip strength and to inhibit apoptosis in aged rats [Xu et al, 2010].…”
Section: What We Expect From Coq Deficiency and Supplementationmentioning
confidence: 99%